Design and building system analysis on the smart fisheries village (SFV) website at the banyuwangi fisheries training and counseling center - Khotijah, Adinda Inne; Solehatin, Solehatin (SHM Publisher, 2024)
This research aims to analyze and design a smart fisheries village-based website system to facilitate back-end, front-end, and UI/UX designers in the application of website creation according to the needs desired by the agency and with an organized database so that the creation of data reports will be faster. The early stages of the research began with the identification of the the specific needs of fishing villages and involved an in-depth analysis of the system needs that supported the vision of the Smart Fisheries Village. The design began with data collection consisting of observation methods and interviews, where researchers interviewed the authorities. In this method, the author gives 5 questions to the user, data analysis, and design of the Unified Modeling Language (UML). The design of this SFV web system uses a Unified Modeling Language (UML), which involves the use of diagrams and UML notation to describe various aspects of the system visually. The results of this study include UML diagrams, which encompass activity diagrams (for users and admins), flow diagrams (for users and admins), use case diagrams (for users and admins), and class diagrams that have undergone 4-5 iterations. The design of the Smart Fisheries Village website system is necessary to improve the welfare of the fishing village. Contributions of this research include the standardization of modeling, increased productivity, improved analysis and planning, and improved understanding. Previous research might have concentrated on a single type of system or domain. However, research should be expanded to various types of systems and industries.